2007
DOI: 10.2333/bhmk.34.45
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Relationship Between Psychosocial Variables and Diurnal Cortisol Rhythm Under Chronic Stress by Using Structural Equations

Abstract: By using structural equations, we investigated the effect of chronic stress on salivary cortisol rhythm and proposed a causal model of chronic stress by using psychosocial and physiological data. First, 111 healthy workers (48 males, 63 females) completed questionnaires on chronic stress and lifestyle habits. Then, they provided saliva samples and answered questionnaires that were prepared to assess their psychological states 5 times (on waking up and at 10:00, 11:40, 14:00, and 16:00) on workdays. Structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Comparisons across different modes of commuting were also found to be influential; for example, nurses using public transportation were more willing to change their job than those using private transportation (i.e., their own car; Festini et al, 2011). Although a physically active commute mode (e.g., biking to work, walking to work) was commonly evaluated in terms of the benefits of active commuting, one study found that women who actively commute were more likely to be sedentary while at work (Ohta et al, 2007). Finally, some papers that included multiple studies did not find consistent relationships across studies (e.g., commute time and job satisfaction, Morrow, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons across different modes of commuting were also found to be influential; for example, nurses using public transportation were more willing to change their job than those using private transportation (i.e., their own car; Festini et al, 2011). Although a physically active commute mode (e.g., biking to work, walking to work) was commonly evaluated in terms of the benefits of active commuting, one study found that women who actively commute were more likely to be sedentary while at work (Ohta et al, 2007). Finally, some papers that included multiple studies did not find consistent relationships across studies (e.g., commute time and job satisfaction, Morrow, 2010).…”
Section: Resultsmentioning
confidence: 99%